Women and Water: The Flow of Matriculture: Introduction (English) - Rowlatt, Linnéa; Guédon, Marie-Françoise (Matrix, 2025)
The relationships between women and water are deep and fluid, informing the definition of the feminine, the roles assigned to women, and the very perception of life. This issue of Matrix seeks to explore certain aspects of these relationships and the ways in which women interpret symbolic systems to position themselves as actors in the great concrete game of relationships with the environment as a whole. In this issue, our authors examine the relationship between women and water among peoples of North America, Northern Europe, Nigeria, the Italian Alps, and Cameroon. Through mythology, personal experience, art, and ritual, they explore the different expressions of this relationship, which constitutes an important part of the lives of communities past and present.